Ventilation Modeling of Cavern with Cfd - Hurtado-Cruz, J; Vargas-Norambuena, J; Jarufe-Troncoso, J; Perez-Cortes, S; Carvajal-Meza, M (Springer Science and Business Media Deutschland GmbH, 2024)
Mine ventilation and underground works have seen extensive worldwide development, which has been studied for the past century, producing extensive and rigorous results that currently aid in safely performing underground operations of different kinds and characteristics. However, there have been relatively few open studies on cavern ventilation, which has tended to be part of engineering studies without further disclosure. In general terms, the intended use of the cavern determines the ventilation system to be used according to heat and pollutant sources, additionally to the geometry and size. In this regard, the present work aims to define elementary ventilation aspects for underground caverns linked to construction systems, to avoid dead spaces without air movement inside. Computational fluid mechanics is used as a simulation and analysis tool, generating various simulation scenarios. The results show different ventilation styles according to the established boundary conditions and the construction facilities as access drifts, which helps to set the inlets and outlets and could help to orientate future ventilation designs. © Society for Mining, Metallurgy & Exploration Inc. 2024.